The Effect of Work-Life Balance and Self-Efficacy on Burnout in Working Students (Study of 2020 Undergraduate Students at the Faculty of Economics and Business, Semarang State University) - Hanan Maulana; Anindya Ardiansari (Universitas Negeri Semarang, 2024)
This study aims to determine the effect of work-life balance and self-efficacy on burnout in 2020 FEB students at Semarang State University with the Burnout Syndrome Theory approach. A quantitative approach was used with a population of working students of the Faculty of Economics and Business class of 2020. A sample of 100 respondents was taken using purposive sampling technique based on Lemeshow's formula. Data were collected through questionnaires and analyzed using descriptive analysis, classical assumption test, model accuracy test, multiple linear regression analysis, and hypothesis testing through IBM SPSS version 25.0. The results showed that work-life balance and self-efficacy have a significant positive effect on burnout in working students of the Faculty of Economics and Business class of 2020. This means that the better the work-life balance and self-efficacy of students in dealing with academic and work tasks, the higher the level of burnout felt. This study suggests adding other independent variables that affect burnout as well as using a larger sample and not limited to the Faculty of Economics and Business class of 2020.